Beyond the Screen: The Lived Experiences of College Seminarians Facing Speaking Anxiety in Online English Classes - Christine Anne G. Abling-Salupen; Constantino T. Ballena (Philippine Social Science Journal)
This study investigated the speaking anxiety experienced by college seminarians in online English classes. The research aimed to describe the causes, effects, and coping strategies related to this anxiety. Using a hermeneutic phenomenological approach, data were collected through observations, in-depth interviews, and peer debriefing with nine purposively sampled participants. The analysis identified key themes such as fear of judgment, lack of confidence, and negative teaching styles as primary causes of anxiety. Manifestations included increased use of fillers, stuttering, and avoidance behaviors. Participants employed coping mechanisms like positive self-talk, regular practice, and prayer. The study concludes that supportive teaching practices significantly reduce speaking anxiety. Practically, the findings suggest that educators should create positive, interactive learning environments to alleviate anxiety and enhance language acquisition. Future research should explore speaking anxiety in diverse educational contexts and develop targeted interventions to mitigate this issue further.